To Protect or Not to Protect: Finnish Translators’ Perceptions on Translator Status and Authorisation - Ruokonen, Minna (HERMES - Journal of Language and Communication in Business, 2018)
In most countries, there are no restrictions on who is allowed to work as a translator, apart from the context of legally valid or authorised translations. Nevertheless, the significance of authorisation for translator status has hardly been studied, apart from Dam/Zethsen (2009, 2010). This article investigates how authorisation affects Finnish translators’ status perceptions, and whether they believe that the profession should be protected further, and if so, how and why. The data come from a survey conducted in 2014 with 450 respondents (business, literary and audio-visual translators), based on Dam/Zethsen’s questionnaires and expanded and adapted for the Finnish context. The analysis is partly quantitative and statistical, partly a qualitative thematic analysis of the respondents’ open comments. Statistically, authorisation produced no significant differences in the respondents’ status perceptions. Similarly, in open questions on factors affecting translator status and measures that should be taken, few respondents mentioned authorisation or other professional boundaries. Nevertheless, when asked whether the profession should be protected, almost 60% of the respondents, particularly business translators who had attended translator training, advocated some form of protection, although they also emphasised that there should be flexibility to allow for translators with different backgrounds. The respondents were also more prone to call for protection if they held authorisation themselves, which may suggest that they feel authorisation does carry some value.